Optimizing Outcomes in Urological Surgery: Preoperative Care. Issue 3 (7th May 2020) - Stoffel, John T.; Chrouser, Kristin; Montgomery, Jeffery S.; Suskind, Anne M.; Smith, Angela; Tucci, Christopher; Vanni, Alex J.
Abstract: Purpose: Understanding best practices in preoperative care is critical for quality of care for our urology patients. We compiled a concise resource that provides recommendations for optimizing preoperative outcomes for patients undergoing urological surgery. Materials and Methods: Urological preoperative care was defined as medical evaluation or treatment received in preparation for surgery or a procedure. The Preoperative White Paper Panel was comprised of practicing urologists and nurses. The topic was researched via literature published from 1980 through 2018 which focused on preoperative evaluation and safety. Best practice recommendations were also reviewed from specialty societies. Recommendations in this article reflect expert opinion from the Panel, and are based on review of available evidence and existing best practice statements. Results: Preoperative optimization involves a good assessment and stratification of surgical risk for the patient about to undergo surgery or a procedure. This assessment starts with a timely history and physical evaluation, as well as review of underlying frailty and cognition. The assessment helps inform potential postoperative needs. Risk stratification calculators are available to determine potential cardiac and pulmonary morbidity as well as overall surgical risk. Optimization of endocrine and gastrointestinal comorbidities can also reduce complications for patients. Modifiable preoperative behaviors and needs such as malnutrition and smoking cessation should also be discussed before surgery. Conclusions: We summarize the preoperative factors that may impact surgical outcomes in urology. By understanding and applying best practices for preoperative care, urologists can optimize the quality of care for their patients